Pengaruh Pengetahuan Akuntansi Syariah Dan Kepribadian Wirausaha Terhadap Kinerja Baitul Maal Wat Tamwil - Umi Sa'idah; Taufik Akbar (Jurnal Pena-Mas Akuntansi, 2022)
This study aims to examine the effect to knowledge of sharia accounting and entrepreneurial to the managerial performance of Baitul Maal wa Tamwil. The population in this research are manager and staff of financing in BMT located in DKI Jakarta, Banten, dan West Java. The sampling method is using Stratified Random Samping and obtained sample of 42 respondents in 35 BMT. Eksogen Variable Laten from this study is knowledge of sharia accounting dan entrepreneurial, and Endogen Variable Laten is managerial performance. The required data in the research is primary data through questionnaires distributed directly to the respondents. The method of data analysis is using Structural Equation Modeling (SEM). Data processing is using application program Smart Partial Laest Square (SmartPLS) versi 3.0. The results of this study indicate that variables of knowledge of sharia accounting doesn’t has a significant effect on managerial performance of BMT, while the variable of entrepreneurial personality have a postivie and significant effect on managerial performance of BMT in DKI Jakarta, Banten, and West Java.